10.1016/s0197-2510(10)70184-4 (CrossRef Listing of Deleted DOIs, 2000)
AIM: Several first-line immunotherapy-based regimens are available for patients with programmed death ligand 1 positive advanced or metastatic triple-negative breast cancer, but their relative economic value in China remains uncertain. This study evaluated selected regimens from the perspective of the Chinese healthcare system. METHODS: We developed an exploratory cross-trial partitioned survival model using survival data from the IMpassion130, KEYNOTE-355, TORCHLIGHT, and ASCENT-04 Phase III trials, with utility and cost inputs from published sources and the Chinese healthcare setting. Outcomes included total costs, life-years (LYs), quality-adjusted life-years (QALYs), and incremental cost-utility ratios. Pairwise comparisons used a willingness-to-pay threshold of USD 43,333 per QALY. RESULTS: Pembrolizumab plus Sacituzumab Govitecan yielded the most LYs and QALYs, but at the highest cost. Toripalimab plus chemotherapy had the lowest cost, produced health outcomes similar to those of Pembrolizumab plus chemotherapy, and had the most favorable economic profile at the prespecified threshold. Pembrolizumab plus chemotherapy was cost-effective versus Atezolizumab plus chemotherapy. Pembrolizumab plus Sacituzumab Govitecan was not cost-effective, as its limited incremental benefit did not offset its substantially higher cost. Sensitivity analyses generally supported the base-case findings. CONCLUSIONS: Among the regimens evaluated, Toripalimab plus chemotherapy provided the most favorable balance between costs and health outcomes in China. Pembrolizumab plus chemotherapy also offered reasonable economic value versus Atezolizumab plus chemotherapy, whereas the value of Pembrolizumab plus Sacituzumab Govitecan was constrained by its high acquisition cost.